The circular dichroism properties of φW-14 DNA containing α-putrescinylthymine - Spetter, Susan; Chen, Catherine; Warren, R.A.J.; Hanlon, Sue (Biochimica et biophysica acta, 1985)
The circular dichroism properties of φW-14 DNA containing α-putrescinylthymine and its acetylated derivative have been examined in a number of aqueous solvents. Native φW-14 DNA exhibits a B-type CD spectrum whose characteristics do not entirely conform to what would be expected for its GC content (51%). The conformationally sensitive positive band above 260 nm has a rotational strength greater than that normally found in prokaryotic DNAs of comparable GC content, such as Escherichia coli DNA. The rotational strength of this band in the spectrum of the heat-denatured from of φW-14 DNA, however, is similar to that of heat denatured E. coli DNA. Abolition of the positive charge on the putrescine residues of native φW-14 DNA by reaction with CH 2O or by acetylation reduces the rotational strength to a level appropriate for its GC content. Increases in the electrolyte content of the solvent have the same effect, although the rotational strength of this band in φW-14 DNA does not become comparable to that of E. coli DNA until 6–7 M LiCl. Titration to pH 10.6 in solvents of modest electrolyte content, however, fails to appreciably affect the CD spectral properties of either native φW-14 DNA or the derivative in which half of the secondary and all of the primary amino groups have been acetylated. On the basis of these results we have concluded that the enhanced rotational strength of the positive band above 260 nm in the CD spectrum of φW-14 DNA is due to a conformational difference caused by an ion-pair interaction of the positively charged primary amino groups of putrescine with the phosphate backbone. The CD spectral properties, however, reveal that these differences, averaged over the entire basepair population, appear to be relatively small. The average conformation, at least in dilute aqueous solutions, seems to be an unexceptional B variant with conformational properties which would be more appropriate for a DNA of higher CG content.